Accelerating the startup of microbial fuel cells by facile microbial acclimation. (December 2019) - Zhang, Ping; Yang, Cuicui; Xu, Yu; Li, Hai; Shi, Wei; Xie, Xiaoji; Lu, Min; Huang, Ling; Huang, Wei
Abstract: Rapid startup of microbial fuel cells (MFCs) is critical for the practical application of MFCs, while it is still challenging to quickly initiate newly fabricated MFCs. Herein, we show that a simple yet handy strategy for acclimating the inoculum, by modulating brightness, anoxic environment and the presence of carbon powder, can accelerate the startup of MFCs. Using acclimated inoculums, the startup time of MFCs can be reduced to 43 h which is shortened by 63.2% than that of MFCs using unacclimated inoculums, while maximum power densities are well maintained (649–724 and 669 mW m − 2 by using acclimated and unacclimated inoculums, respectively). Further studies show that the acclimation can induce the generation of conductive bacterial nanowires and increase the Rhizobiales population. Accordingly, we reason that conductive bacterial nanowires and the metabolically versatile Rhizobiales can synergistically facilitate the irreversible attachment of bacteria and subsequent biofilm formation, and therefore accelerate the startup. Graphical abstract: Unlabelled Image Highlights: Acclimation of the inoculum can shorten the startup of microbial fuel cells (MFCs). Acclimating inoculums in bright and anoxic conditions reduces startup time by 63.2%. Conductive bacterial nanowires appear on bacteria acclimated under anoxic condition. The Rhizobiales population increases in inoculums acclimated under bright condition. The nanowires and Rhizobiales in the inoculum can facilitate the startup of MFCs.